Managing environmental innovation: Case study on biorefineryconcept - MarouÅ¡ek, Josef; MyÅ¡ková, MyÅ¡ková; Å½ákJaroslav (Revista Técnica da Faculdade de Engenharia da de Zulia, 2015)
Â A brief report on the long path from fundamental studies to applied research, prototype development, samples testing and the construction of the commercial scale biorefinery is provided. Condensed technical and financial assessments are presented. Processing parameters were robustly analyzed in order to increase the surface area of the pyrolysis residue from different biowaste for its better subsequent utilization in the building industry. Finally, it is noted that research and innovation are the key moments to improve the overall competitiveness of firms and countries too.